2019
DOI: 10.1111/1750-3841.14653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Accelerated Storage on Fatty Acids, Thermal Properties and Bioactive Compounds of Kenaf Seed Oil

Abstract: The effects of thermal oxidation at 65 °C for 24 days on oxidation indices, fatty acid positional distribution, thermal properties, vitamin E composition and sterol composition of kenaf seed oil are investigated. The results showed that total oxidation value (TOTOX) of the oil increased from initial 8.83 to 130.74 at the end of 24 days storage. Linoleic acid at sn‐1, 3 positon of kenaf seed oil was less stable than the one at sn‐2 positon. Oxidative degradation changed the melting profile of kenaf seed oil, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In general, POV indicates the amount of primary oxidation products, while TBARS and pAV are indicators of formation of secondary oxidation products (Zhang et al ., 2019). The oxidative stability of the fish oil samples (with and without antioxidants) heated at 80 °C for 12 days was evaluated by measuring their POV, TBARS and pAV values.…”
Section: Resultsmentioning
confidence: 99%
“…In general, POV indicates the amount of primary oxidation products, while TBARS and pAV are indicators of formation of secondary oxidation products (Zhang et al ., 2019). The oxidative stability of the fish oil samples (with and without antioxidants) heated at 80 °C for 12 days was evaluated by measuring their POV, TBARS and pAV values.…”
Section: Resultsmentioning
confidence: 99%
“…In general, POV is a quantitative index of primary oxidation products, while TBARS and p AV reflect the amount of secondary oxidation products ( Zhang et al, 2019 ). The POV, TBARS and p AV values of the fish oil samples with and without antioxidants during the accelerated storage at 80 °C were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported similar results aer storage tests; the decrease in UFA (including PUFA and MUFA) content and the increase in SFA content could be associated with oil oxidation. 53,54 During the oil oxidation process, the PUFA is gradually oxidised to MUFA and subsequently to SFA. 26,53 In contrast, CPE extracted pumpkin seed oil had a higher PUFA loss rate than that extracted by SE and AEE, indicating that the former may be more oxidised.…”
Section: Oxidative Stabilitymentioning
confidence: 99%
“…53,54 During the oil oxidation process, the PUFA is gradually oxidised to MUFA and subsequently to SFA. 26,53 In contrast, CPE extracted pumpkin seed oil had a higher PUFA loss rate than that extracted by SE and AEE, indicating that the former may be more oxidised. Taking together, it was indicated that AEE and SE had relatively higher oxidative stability than CPE, with AEE performing the best.…”
Section: Oxidative Stabilitymentioning
confidence: 99%